From Integration to Resilience: Rethinking Euro-Atlanticism in the Post-Ukraine European Order - Maksuti, Bekim (European Scientific Journal, ESJ, 2025)
This article examines how the 2022 Russian invasion of Ukraine reshaped Euro-Atlantic security by accelerating a shift from institutional integration toward resilience-based strategic thinking. Using qualitative analysis of NATO and EU strategic documents, academic literature, and regional policy assessments, the paper evaluates how small states - particularly in the Western Balkans - adapt within this evolving order. The findings show that post-2022 Euro-Atlanticism increasingly depends on internal political cohesion, institutional integrity, and societal resilience, rather than on integration alone. The analysis highlights that the “resilience turn” has moved Euro-Atlantic cooperation from expansion toward consolidation, placing equal emphasis on the protection of democratic institutions, societal stability, and the ability to counter hybrid threats. For small states such as North Macedonia, this shift underscores that credibility within alliances derives not only from formal membership but from sustained reform capacity, predictability, and proactive regional engagement. The paper further demonstrates that the Western Balkans operate as a critical periphery where geopolitical competition, internal vulnerabilities, and Euro-Atlantic commitments intersect, making resilience a strategic necessity rather than a normative aspiration. The study concludes that the sustainability of the Euro-Atlantic system will rely on a deeper alignment between collective deterrence and domestic reform capacities among small member and partner states, as well as on their ability to translate alignment into functional stability and regional cooperation.